Case Report: Physiological and psychological underpinnings of muscle dysmorphia using EEG, GSR, and eye-tracking - Metin Çınaroğlu; Selami Varol Ülker; Eda Yılmazer; Gökben Hızlı Sayar (Frontiers in Psychology, 2025)
BackgroundMuscle dysmorphia (MD), a subtype of Body Dysmorphic Disorder (BDD), involves an obsessive preoccupation with perceived insufficient muscularity despite an objectively muscular physique. While its psychological features are well-documented, physiological and attentional underpinnings remain underexplored.ObjectiveThis exploratory, proof-of-concept case series examines the psychological, physiological, and attentional characteristics of individuals with varying experiences of MD using a multimodal approach combining electroencephalography (EEG), galvanic skin response (GSR), and eye-tracking technologies.MethodsThree male participants were purposefully selected to represent distinct clinical profiles: one with active MD and steroid use, one in sustained remission from MD, and one with no MD history. Participants completed validated psychological scales (MDDI, BIDQ, STAI, RSES) and were exposed to personalized visual stimuli (past, current, and idealized body images). A triangulated recording protocol was used to capture EEG, GSR, and eye-tracking data during stimulus exposure.ResultsParticipants with current and past MD showed elevated beta wave activity, increased skin conductance, and attentional biases toward muscular regions, corresponding with higher self-reported distress and anxiety. In contrast, the control participant exhibited stable physiological responses and emotionally neutral reactions. Triangulated data revealed coherent patterns across subjective and physiological domains, supporting the internal validity of the findings despite the small sample.ConclusionThese findings illustrate the potential of multimodal assessment in identifying candidate psychophysiological markers of MD. While not generalizable, this case-series provides a valuable framework for future hypothesis-driven research and supports the need for gender-specific diagnostic and intervention strategies in muscle dysmorphia.